Inhalable Composite Microparticles Containing siRNA-Loaded Lipid-Polymer Hybrid Nanoparticles: Saccharides and Leucine Preserve Aerosol Performance and Long-Term Physical Stability - Xu, You; Turan, Enise Tugba; Shi, Zhenning; Franzyk, Henrik; Thakur, Aneesh; Foged, Camilla (Frontiers in Drug Delivery, 2022)
Thermostable dry powder formulations with high aerosol performance are attractive inhalable solid dosage forms for local treatment of lung diseases. However, preserved long-term physical stability of dry powder inhaler (DPI) formulations is critical to ensure efficient and reproducible delivery to the airways during the shelf life of the drug product. Here, we show that ternary excipient mixtures of the disaccharide trehalose (Tre), the polysaccharide dextran (Dex), and the shell-forming dispersion enhancer leucine (Leu) stabilize siRNA-loaded lipid-polymer hybrid nanoparticles (LPNs) during spray drying into nanocomposite microparticles, and result in inhalable solid dosage forms with high aerosol performance and long-term stability. The stabilizing roles of Tre and Dex were also studied separately by investigating DPI formulations containing binary mixtures of Leu/Tre and Leu/Dex, respectively. DPI formulations containing binary Leu/Dex mixtures were amorphous and displayed preserved long-term physical stability of LPNs and chemical stability of siRNA in accelerated stability studies under exaggerated storage conditions (ambient temperature and relative humidity). In contrast, powders containing binary Leu/Tre mixtures were amorphous, and hence metastable, and were recrystallized after six months of storage. Ternary mixtures of Tre, Leu, and Dex provided the most efficient protection of the LPNs during the spray drying process and prevented recrystallization of amorphous Tre. Hence, in ternary mixtures, Leu, Tre, and Dex have the following functions: the shell-forming Leu functions as a dispersion enhancer and is essential for high aerosol performance, the disaccharide Tre provides LPN protection during manufacturing and storage due to efficient coverage of the LPN surface, and the polysaccharide Dex promotes the formation of porous particles and prevents recrystallization of Tre during long-term storage. Therefore, the use of ternary excipient mixtures composed of Leu, Tre, and Dex, may prevent instability problems of DPI formulations and preserve the aerosol performance during long-term storage, which is essential for effective pulmonary drug delivery.